Struktur Tegakan dan Tutupan Kanopi Ekosistem Hutan dan Parak di Kecamatan Lubuk Kilangan Kota Padang - Zikri, Muhammad; Reki Kardiman (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study aimed to determine the stand structure and tree canopy cover in forest and parak ecosystems in Lubuk Kilangan District, Padang City. This is a descriptive research with a direct observation throught purposive random sampling method. Data were collected by making six of 20 x 20 m plots in each primary forest and parak ecosystem. Tree diameters ≥10 cm were measured in each plot and canopy cover were collected using the Hemispherical Photography method using a mobile phone front camera equipped with a fish-eye lens. Data were analyzed in terms of stand density, basal area, Stand Basal Area (SBA), and percentage of canopy cover. The average tree density in the primary forest area was 913 individuals/ha, while the tree density in the parak was 467 individuals/ha. The SBA value in the primary forest was higher than in the parak, which was 64.10 m2/ha in the primary forest and 14,72 m2/ha in the parak. The average percentage of canopy cover in both areas shows that the percentage of primary forest canopy cover was greater than that of parak. The average value of the percentage of canopy cover in the forest area was 80.48%, while in the parak area was 71.23%. Correlation between tree density, canopy cover, SBA was only occured in primary forest area where the canopy cover negatively correlated with SBA. This study showed that the primary forest area and parak in Lubuk Kilangan Subdistrict have a good tree density, SBA and tree canopy covers.